Trophic contamination by octocrylene does not affect aerobic metabolic scope in juveniles clownfish - Julie Lucas; Valentin Logeux; Alice MS Rodrigues; Didier Stien; Philippe Lebaron (Annals of Environmental Science and Toxicology - Peertechz Publications, 2020)
The effect of trophic exposure to Octocrylene (OC) on aerobic metabolism of clownfish Amphiprion ocellaris was investigated. There were no significant differences in Standard Metabolic Rate (SMR), Active Metabolic Rate (AMR) or aerobic metabolic scope (AS) at the concentration of 10 µg/g of octocrylene in diet of juvenile's clownfish whatever the time of exposure. This suggests that under these experimental conditions, exposure to OC in food at a concentration of 10 µg/g did not influence aerobic metabolism of this species.